2019
DOI: 10.2147/dmso.s204414
|View full text |Cite
|
Sign up to set email alerts
|

<p>Impact of arterial hypertension and type 2 diabetes on cardiac autonomic modulation in obese individuals with recommendation for bariatric surgery</p>

Abstract: Background and aimObese individuals with recommendation for bariatric surgery (BS) exhibit increased cardiovascular risk. The association of obesity with comorbidities, such as arterial hypertension (HTN) and type 2 diabetes mellitus (T2DM) can worsen cardiovascular dysfunction. This study aimed to investigate the effect of HTN on cardiac autonomic function and whether diabetes exacerbates HTN-related impairment of autonomic function in obese subjects.MethodsSamples (n=63) were allocated to three groups: Obese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
7
1
Order By: Relevance
“…Glucose and Lipid dysmetabolism have been associated with impaired HRV and cardiac autonomic dysfunction in obese and NAFLD subjects [15,22]. However, in the present study, the glucose and lipid serum levels did not correlate expressively with worsening of HRV indices; AST serum levels, however, were negatively correlated with SDRR, RMSSD and SD1.…”
Section: Plos Onecontrasting
confidence: 87%
See 1 more Smart Citation
“…Glucose and Lipid dysmetabolism have been associated with impaired HRV and cardiac autonomic dysfunction in obese and NAFLD subjects [15,22]. However, in the present study, the glucose and lipid serum levels did not correlate expressively with worsening of HRV indices; AST serum levels, however, were negatively correlated with SDRR, RMSSD and SD1.…”
Section: Plos Onecontrasting
confidence: 87%
“…The heart rate (HR) and the following measures of HRV analysis were determined; 1) timedomain parameters: average R-R interval, standard deviation between the duration of RR intervals (SDRR), the square root of the mean of the sum of the squares of the successive differences between adjacent normal-to-normal beats (RMSSD), and the number of pairs of successive normal-to-normal beat intervals that differed by 50 ms (pRR50); 2) frequency-domain parameters: low frequency (LF) band (from 0.04 to 0.15 Hz) and high frequency (HF) band (from 0.15 to 0.40 Hz) and the LF/HF ratio, the power of each spectral component was calculated in normalized units (un); 3) Nonlinear parameters (SD1 and SD2). Poincaré scatters plots were constructed and investigated as a nonlinear tool, including the transverse axes (SD1, an indicator of parasympathetic activity) and the longitudinal axes (SD2 a function of sympathetic and vagal activity) [15].…”
Section: Blood Pressure Electrocardiogram Recording and Heart Rate Vmentioning
confidence: 99%
“…In addition, HRV indices are reduced in both the supine and orthostatic standing positions. This shows the imbalance of the cardiac autonomic system that can be related to the development of cardiovascular diseases [19][20][21]. HRV indices were also inversely associated with age, indicating that HRV indices in the time and frequency domains decrease and the LF/HF ratio increases with the increase in age.…”
Section: Discussionmentioning
confidence: 85%
“…It is also used as an indicator of morbidity and mortality [19]. Autonomic imbalance, characterized by a hyperactive sympathetic system and a hypoactive parasympathetic system, is associated with various pathological conditions, including obesity, hypertension and diabetes [19][20][21]. Although cleaners have risk factors for cardiovascular disease, no studies were found investigating HRV in this population.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of overweight and obesity has increased worldwide and is recognized as a chronic disease of complex management and increased risk of morbidity and mortality. 1,2 Early evidence has shown that serum levels of 25-hydroxyvitamin D [25(OH)D] are frequently reduced in obese subjects [3][4][5][6] and that adipose tissue serves as a reservoir for vitamin D, leading to less bioavailability and reduced serum levels. 6,7 An early study demonstrated that obese women have greater adipose stores of vitamin D in subcutaneous and omental comportments.…”
Section: Introductionmentioning
confidence: 99%